Facilitators and barriers of Baduanjin practice in frail kidney transplant recipients: A qualitative study - Yingtian Jia; Changyun Wei; Shaobo Guo; Xinran Yang; Hongxia Liu (Journal of Integrative Nursing)
Objective: To understand the facilitators and barriers for frail kidney transplant recipients (KTRs) practicing Baduanjin, and to provide a theoretical basis for developing intervention strategies. Subjects and Methods: Semi-structured interviews were conducted with 10 frail KTRs who participated in a 3-month Baduanjin practice. The Colaizzi seven-step analysis method was used to analyze, summarize, and extract themes from the interview data. Results: Two themes were extracted: facilitators and barriers. Facilitators included intrinsic motivation and perceived benefits, while barriers included conflicts with practice time, worsening physical condition, lack of immediate benefits, and difficulty integrating into daily life. Conclusion: The practice of Baduanjin by frail KTRs is influenced by various factors. Healthcare professionals should develop personalized intervention plans that take into account these factors and the needs of the patients.